The Influence of The Problem Based Learning (PBL) Model on The Learning Outcomes of Class IV Students on Subtema 2 Diversity in Togetherness SDN 091254 Batu Onom T.A 2023/2024 - Enjelina Simbolon; Rio Parsaoran Napitupulu; Desi Sijabat (MultiTech Publisher, 2023)
Study This aim For know is influence of learning modelsProblem Based Learning (PBL ) towards results Study studentclass IV in subtheme 2 togetherness in diversity SDN 091254 Batu Onom . Type of research This that is study quantitative use _ method pre-experiment with form one group pretest-posttest design . Which became sample study This is studentclass IV, totaling 30 students . Instruments used is pretest and posttest tests have been carried out validation and reliability tests were carried out . The research results at the 0.05 level show that exists influence of learning models Problem Based Learning (PBL) to results Study student class IV in subtheme 2 togetherness in diversity of SDN 191254 Batu Onom . Can be seen that results comparison of pretest and posttest sig value is 0.000 which is significant more small from value 0.05, and t has value 16,327. It means there is influence the learning model Problem Based Learning (PBL) to results learn . Change results Study taught students _ with using a learning model Problem Based Learning (PBL) makes it difficultstudent active think , understand The material presented increases the sense of desire know student in seek and findinformation itself , compared with taught students _ withoutusing a learning model Problem Based Learning (PBL).